Trust in International Relations: Rationalist, Constructivist, and Psychological Approaches - Haukkala, Hiski; Wetering, Carina van de; Vuorelma, Johanna (Routledge Global Cooperation Series, 2018)
Trust is a core concept in International Relations (IR), representing a key ingredient in state relations. It was only relatively recently that IR scholars began to probe what trust really is, how it can be studied, and how it affects state relations. In the process three distinct ways of theorising trust in IR have emerged: trust as a rational choice calculation, as a social phenomenon or as a psychological dimension. Trust in International Relations explores trust through these different lenses using case studies to analyse the relative strengths and weaknesses of different approaches. The case studies cover relations between: United States and India ASEAN and Southeast Asian countries Finland and Sweden USA and Egypt The European Union and Russia Turkey's relations with the West This book provides insights with real-world relevance in the fields of crisis and conflict management, and will be of great interest for students and scholars of IR, security studies and development studies who are looking to develop a more sophisticated understanding of how different theories of trust can be used in different situations.